Photosynthetic capacity of senescent leaves for a subtropical broadleaf deciduous tree species Liquidambar formosana Hance - Zidong Luo (Nature Portfolio, 2017)
Abstract Photosynthetic capacity and leaf life span generally determine how much carbon a plant assimilates during the growing season. Leaves of deciduous tree species start senescence in late season, but whether the senescent leaves still retain capacity of carbon assimilation remains a question. In this study, we investigated leaf phenology and photosynthesis of a subtropical broadleaf deciduous tree species Liquidambar formosana Hance in the central southern continental China. The results show that L. formosana has extended leaf senescence (more than 2 months) with a substantial number of red leaves persisting on the tree. Leaf photosynthetic capacity decreases over season, but the senescent red leaves still maintain relatively high photosynthetic capacity at 42%, 66% and 66% of the mature leaves for net photosynthesis rate, apparent quantum yield, and quantum yield at the light compensation point, respectively. These results indicate that L. formosana may still contribute to carbon sink during leaf senescence.